Using the One Drop Penetrability Method to Express Soil Compaction at the Forest Landscape Restoration Sites along Batang Kayan Ulu, Sarawak, Malaysia - Mugunthan, Perumal; Mohd Effendi, Wasli; Jonathan, Lat; Latifah, Omar; Zahora, Ismail; Jie Hung, King (2023)
Soil compaction greatly impacts plant growth and mortality rates (Kozlowski, 1999; Hattori et al., 2013). Although mild compaction may be advantageous to plant growth, heavy mechanical use at logging sites and heavy foot traffic in recreational areas typically hinder plant growth, survival, and yield (Alameda and Villar, 2009; Kozlowski, 1999). In Southeast Asia, commercial logging has caused tropical rainforest degradation, and the use of heavy machinery during these operations has exacerbated soil compaction (Hattori et al., 2013). Compaction typically negatively affects soil structure and hydrology by increasing bulk density, soil strength, water runoff, and erosion as well as breaking down soil aggregation, and decreasing porosity, aeration, and infiltration capacity (Bruenig, 1996; Jusoff, 1992; Jusoff and Majid, 1986, 1987; Kozlowski, 1999; Van der Plas and Bruijnzeel, 1993). The main strategy for accelerating the regeneration and rehabilitation of degraded forests is through enrichment planting of logged-over sites with dipterocarp trees (Dipterocarpaceae), which are the dominant canopy species and significant timber sources in Southeast Asian forests (Ådjers et al., 1995; Appanah and Weinland, 1996; Kenzo et al., 2011). However, severe soil compaction may make enrichment planting less successful by reducing the development and survival rates of seedlings that have been planted. One drop penetrability (ODP) is a measure of soil compaction, and it has been discovered that at the research sites, it is highly correlated with root growth to sustain sufficient turgor pressure (Sakurai et al., 1995; Ishizuka et al., 1998; Hattori et al., 2013). Therefore, this study was conducted to evaluate the soil compaction using the one drop penetrability (ODP) method at Shorea macrophylla forest landscape restoration sites along Batang Kayan Ulu, Sarawak, and adjacent secondary forests.